468 A Review of Child Protection Practices in a Busy District General Hospital. (October 2012) - Walsh, C; Livingstone, A; Mulroe, T
Abstract : Background and Aims: Following the tragic death of Victoria Climbié in 2003, Lord Laming produced a report setting out a number of recommendations aimed at improving Child Protection (CP) practices throughout the UK. We decided to review our practice in a District General Hospital in Northern Ireland to determine whether recommendations from previous CP audits were implemented, and in addition check our compliance with the Laming recommendations. Methods: We performed a retrospective chart audit on CP cases presenting to our paediatric department between September 2008 and March 2010. Using recommendations from previous audits and Lord Laming we defined our standards and devised a pro forma for collecting data. Results: Our targets were achieved in a number of areas, in particular medical note keeping, use of CP illustrative templates, documentation of telephone exchanges and face to face discussions, the presence of Nursing Progress Notes, identification of the child's consultant and GP in the medical notes and documentation of results of investigations. We failed to meet our objectives relating to certain aspects of communication, especially taking a history from the child, proper use of interpreters, documenting consent, informing social services in writing and documenting review arrangements. Conclusions: Progress has been made in how we manage these difficult and sensitive child protection cases. However, we have identified a number of areas where we can improve upon our current practice, and have made recommendations that we hope will further aid in safeguarding our children in the future.